Design and Study of a Nanocavity-based One-dimensional Photonic Crystal for Potential Applications in Refractive Index Sensing - Sediq, Khalid N.; Muhammadsharif, Fahmi F.; Ramadan, Simko O.; Sedeeq , Shalaw Z. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
Refractive index (RI) can be used to identify a particular substance and determine its purity and concentration. The RI of glucose solution with various concentrations can be determined using a distributed Bragg reflective (DBR) device containing a nanocavity. The optical property of the reflection spectrum produced by DBR is sensitive to the variation of the refractive index. In this study, a DBR with a cavity width of 220 nm, located in the middle of the device, is designed and used to sense the variation in the refractive index of glucose at different concentrations. The proposed design showed a sharp dip pattern within the reflection spectrum. The wavelength of the absorption peak was found to be sensitive to trivial variations in the refractive index of glucose solution. Results showed that the variation in the refractive index of glucose within the order of Δn = 0.02 has led to a noticeable shift in the absorption spectrum by Δλ = 2.6 nm. Furthermore, the sensitivity of the proposed device was found to be 130 nm/RIU which is considered high compared with those reported in the literature. Hence, the proposed structure can be a promising optical device for chemical ultrasensing applications.